Consumption and Capital Mobility in the Nordic Countries - Sara Lindberg (Uppsala University, Department of Economics, 1999)
I use a consumption-based test to examine the importance of income constraints and the degree of capital mobility across the Nordic countries over the period 1968-96. In particular, I explore the effects of financial deregulation of the 1980s. The estimating equation is derived along the lines of Bayoumi and MacDonald (1995). The results indicate that Nordic financial markets are highly integrated, but that the consumption behavior of a significant part of the Nordic population is constrained by income. There is no evidence that financial deregulation altered the consumption behavior of households or increased the degree of capital mobility across countries.
urn:nbn:se:uu:diva-2445
Keywords: E21; F36; 330; Consumer behavior; international capital mobility; financial deregulation; Finanzmarktregulierung; Kapitalmobilität; Konsumentenverhalten; Konsum; Nordeuropa